Resurrected right, disorientated left: Pre‐crisis economics and post‐crisis emotions. Issue 3 (December 2015) - Berry, Craig
Abstract : The Conservative party's ability to embrace popular concerns around value, place and equality has enabled it to resurrect the old pre‐crisis growth model, saysCraig Berry, in a move which none of the post‐crisis narratives offered by the Labour party has yet been able to disrupt or overturn.